Protein carbonyls and protein thiols in rheumatoid arthritis - P., Pullaiah; M. M., Suchitra; B., Siddhartha Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Oxidative stress (OS) has an important role in the pathogenesis and progression of rheumatoid arthritis (RA). OS causes protein modification, thereby impairing the biological functions of the protein. This study was conducted to assess the oxidatively modified protein as protein carbonyl content and the antioxidant status as protein thiols, and to study the association between protein carbonyls and protein thiols in RA. Methods: Newly diagnosed RA patients who were not taking any disease modifying anti-rheumatic drugs were included into the study group (n=45) along with age and sex matched healthy controls (n=45). Serum protein carbonyl content and protein thiols were estimated. Results: Elevated protein carbonyl content and decreased protein thiol levels (p<0.001) were observed in RA. A significant negative correlation was observed between protein carbonyl content and protein thiol levels (p<0.001). Conclusions: Oxidative stress in RA is evidenced by enhanced protein oxidation and decreased antioxidant protein thiol levels. Decreased protein thiols may also reflect protein modifications leading to compromise in the antioxidant properties. This oxidant and antioxidant imbalance needs to be addressed by therapeutic interventions to prevent disease progression.